INSTITUTIONAL DISTINCTIVENESS; THE ROLE OF UNIQUE SELLING PROPOSITIONS IN EDUCATIONAL MARKETING - Feriska Listrianti (Nurul Jadid University, 2024)
This study explores the important aspects of the uniqueness of educational institutions through the concept of Unique Selling Propositions (USP) in the context of effective marketing. Using a qualitative approach, this study aims to explore how a well-defined USP can serve as a differentiation tool for educational institutions and influence the decisions taken by prospective students and parents. The data collection process was carried out through in-depth interviews with various stakeholders, including educators and parents, and analysis of marketing documents implemented by the institution. The study's results revealed that a clear USP not only enhances the institution's image but also significantly contributes to increased enrollment and student loyalty. The emphasis on aspects such as innovation in the curriculum, an inclusive learning environment, and a track record of successful graduates has been shown to positively impact attracting a wider audience. This study presents a new perspective on the significance of USP in educational marketing strategies. It underlines the need for ongoing evaluation to ensure that the strategy remains relevant and effective in the face of the dynamics of the ever-changing educational market needs.